Pelatihan Wawancara Kerja Human Resource Department (HRD) untuk Pembekalan Tes Kerja - Aisyiah Restutiningsih Putri Utami; Ermita Ermita; Aufa Maulida Fitrianingrum; Tika Putri Agustina; Melyatul Aini; Kurniahtunnisa Kurniahtunnisa (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
The aim of this Community Service Program (PkM) is to provide job interview training according to human resource department (HRD) standards. The target of this training activity is job applicants who are members of the telegram group. This community service activity uses direct exposure/presentation methods, interview simulation practices, and questions and answers. The background to this training activity is an analysis of community needs by conducting initial observations and interviews via a telegram group. Based on the results of observations and interviews, it was found that there were still many job applicants who failed the job interview test stage. This is due to a lack of experience in interview tests and a lack of knowledge about interview material and assessments. There is also a lack of knowledge about the importance of personal branding. Therefore, training is needed, especially on creating curriculum vitae and LinkedIn for personal branding, interview tips, and tricks, followed by a job interview simulation by 4 (four) participants. The stages of this community service activity are analyzing community needs through observation and interviews, selecting topics for service activities, determining technical activities and creating training materials, presenting training materials, and finally the evaluation stage. Based on the activities that have been carried out, the results obtained show that participants' interview and communication skills have increased in facing job interview tests.